Developmental pathways of Para athletes - Srdjan Lemez; Nick Wattie; Nima Dehghansai; Joseph Baker (Bern Open Publishing, 2020)
This study examines developmental history data to identify common pathways for elite Para sport performance and contextualizes these findings using known models of athlete development (e.g., the Developmental Model of Sport Participation, Côté, 1999). Seventy-three Canadian wheelchair basketball players completed a modified version of the Developmental History of Athletes Questionnaire (Hopwood, 2013). Overall, the results emphasized considerable variability in measures related to 'other' organized sport participation regardless of disability status and competition level, including the proportion of participants that participated in at least one other sport, the number of other sports participated in, the age first participated in other sports, and the number of years spent participating in other sports. This variability suggests there may be multiple Para athlete development narratives and highlights a need for more evidence-based models that are sufficiently nuanced for this athlete cohort.